Proceedings of the 17th ACM Conference on Computer Supported Cooperative Work &Amp; Social Computing 2014
DOI: 10.1145/2531602.2531722
|View full text |Cite
|
Sign up to set email alerts
|

Social influences on secure development tool adoption

Abstract: Security tools can help developers build more secure software systems by helping developers detect or fix security vulnerabilities in source code. However, developers do not always use these tools. In this paper, we investigate a number of social factors that impact developers' adoption decisions, based on a multidisciplinary field of research called diffusion of innovations. We conducted 42 one-on-one interviews with professional software developers, and our results suggest a number of ways in which security … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
83
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(101 citation statements)
references
References 37 publications
(32 reference statements)
5
83
2
Order By: Relevance
“…For a more detailed discussion of our methodology, please see our previous paper drawing on this study [11].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For a more detailed discussion of our methodology, please see our previous paper drawing on this study [11].…”
Section: Methodsmentioning
confidence: 99%
“…In a previous paper [11], we used the same 42 interviews described in the present paper to examine social factors influencing security tool adoption. We direct the reader to that paper for our description of Social System and Communication Channel factors.…”
Section: Related Workmentioning
confidence: 99%
“…to allow practitioners to provide feedback based on their personal experience. We decided not to ask about the willingness to adopt because other research has shown that adoption depends on many different factors (social, cultural, and educational factors, exposure, and many more [7] [8]), which are often external to the actual research. A reliable assessment of the adoptability would require a significant time commitment by practitioners.…”
Section: Ratings Of Research Ideas (Seementioning
confidence: 99%
“…Asking about adoption assumes the availability of tools, which is not always the case, e.g., for empirical papers. In addition, adoption typically depends on different factors, e.g., social, culture, education, exposure, and many more [7] [8], which often are external to the actual research. These issues make it difficult for developers to provide objective assessments of the adoptability.…”
Section: Limitationsmentioning
confidence: 99%
“…It would be particularly interesting to determine those measures used in open source product development because there the use of measurement tools is fundamentally regulated in a different way. While tool choice is often affected by corporate regulations and standards (Xiao et al 2014), open source developers are more likely to have greater freedom in their choice of tools.…”
Section: Validity Threatsmentioning
confidence: 99%